Penerapan Metode CRT Untuk Memupuk Antusiasme Belajar Siswa Kelas Iv Dalam Materi Aktivitas Permainan SDN Pakis 1 Surabaya Tahun Pelajaran 2024/2025 - Ramadhan Ramadhan; Anung Priambodo; Marsudianto Marsudianto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to enhance the learning enthusiasm of 4B grade students at SDN Pakis 1 Surabaya in Physical Education, Sports, and Health (PJOK) through the implementation of traditional games, specifically